Analisa dan Pengujian Penguat Jaringan Seluler 3G Dengan Kabel Feeder Pada Gedung Cyber 2 Tower - Alhanif Fairuszabadi; Dian Kasoni (Jurnal Teknik Informatika, 2019)
Abstract — Indoor Building Coverage (IBC) construction is one of the additional jobs for each operator to improve service quality due to signal attenuation from outside into the building. Cyber 2 Tower is one of the office buildings that will implement IBC development as a form of network service to customers. The performance of the IBC network that will be installed in the Cyber 2 Tower building will be analyzed and tested using hardware and software provided by PT. Bentala Sakti Globalindo as standardization in selling cellular signal booster services. In this study IBC network signal quality in the Cyber 2 Tower building was measured by conducting idle drive test mode using TEMS software already installed on sonyericsson K800i mobile phone which will be adjusted to the calculation previously made by the Cellular operator. From the measurement result obtained for GSM network with EIRP value 18,572 dBm yield RxLevel value equal to -39 dBm and EIRP of 14,062 dBm yield RxLevel value equal to -83 dBm. So the greater the value of Effective Isotropic Radiated Power (EIRP) generated antenna omni and antenna panel will be the better signal quality produced. Similarly, the smaller the value of EIRP generated antenna omni and antenna panel will be worse also the quality of the resulting signal.